Фелікс де Рібас та його "Короткі відомості про торгівлю Одеси" - Феденко, О. (Чорноморська минувшина, 2018)
Вперше пропонується до уваги переклад з італійської мови доповідної записки Фелікса де Рібаса «Короткі відомості про торгівлю Одеси» («Succinta nozione sul commercio di Odessa»), підготовленої на запит сицилійського посла в Петербурзі, герцога ді Серакапріола, у 1813 р. Документ зберігається у фонді Міністерства іноземних справ Державного архіву Неаполя. У доповіді Ф. де Рібас висвітлює особливості одеського ринку та надає поради для кращої проведення торгівельних операцій. Автор також подає довідкову інформацію: основні товари експорту й імпорту, ціни на них, інформацію про російські ваги і міри тощо. The consular correspondence provided insight in commercial life in Odesa, held light on the role of a general consul in providing of international trade between the Russian Empire and the Kingdom of the Two Sicilies. Therefore, the diplomatic archive of the Neapolitan consulate in Odesa contains extremely valuable sources for researching the history of Italian community, diplomatic and commercial life of Southern Ukraine. The Italian translation of the memorandum of Felix de Ribas, «Succinta nozione sul commercio di Odessa», prepared at the request of the Sicilian ambassador in St. Petersburg, the Duke of Seracapriola, was proposed in 1813. The document is kept in fund the Ministry of Foreign Affairs of the State Archives of Naples. In the report, Felix de Ribas highlights the peculiarities of the Odessa market and provides advice for better trading. The author also provides background information: basic goods of export and import, information about Russian scales and measures, etc. Further identification and research of the reports of the foreign consuls and merchant about trades in Odesa will provide a comprehensive opportunity to highlight gaps in economic history of the Southern Ukraine. Предлагается перевод с итальянского языка доклада Феликса де Рибаса «Краткие сведения о торговле Одессы» («Succinta nozione sul commercio di Odessa»), подготовленной на запрос сицилийского посла в Петербурге, герцога ди Серакаприола, в 1813 году. Документ хранится в фонде Министерства иностранных дел Государственного архива Неаполя. В докладе Ф. де Рибас освещает особенности одесского рынка и дает советы, как проводить здесь торговые операций. Автор также дает справочную информацию: основные товары экспорта и импорта, цены на них, информацию о российских веса и меры и т.д.